UJI DAYA HAMBAT VIRGIN COCONUT OIL (VCO) TERHADAP PERTUMBUHAN Candida albicans SECARA IN VITRO - Yunarti, Elsa (IAIN Batusangkar, 2010)
This research was found effectivity and correlation Virgin Coconut Oil (VCO) on number of growth Candida albicans in vitro incubation. Dilution method was use to dilute suspension of C. albicans on Sabouraud's medium. Then, C. albicans was account at 37°C in 24-48 hours incubation. Bioactivity test were replicated three times. Data analysis used SPSS for window 12. One-Way Anova and correlation test use to differ treatment. The research was found number of C. albicans was lower with add of VCO. This result was different at (p<0,05). Correlation test was conducted number of VCO with C. albicans. Then, VCO was effective to defect of growth C. albicans in vitro incubation and there were correlation number of VCO with C. albicans on Sabouraud's medium.Key word: virgin coconut iil, Candida albicans, effectifity, incubation in vitro